2012
DOI: 10.1007/s11434-012-5487-2
|View full text |Cite
|
Sign up to set email alerts
|

Redox modulated hydrogelation of a self-assembling short peptide amphiphile

Abstract: Hydrogels resulting from the self-assembly of small peptides are smart nanobiomaterials as their nanostructuring can be readily tuned by environmental stimuli such as pH, ionic strength and temperature, thereby favoring their practical applications. This work reports experimental observations of formation of peptide hydrogels in response to the redox environment. Ac-I 3 K-NH 2 is a short peptide amphiphile that readily self-assembles into long nanofibers and its gel formation occurs at concentrations of about … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 39 publications
1
25
0
2
Order By: Relevance
“…Replacing the Cys by a Met residue allows the formation of nanofibers at 1.7 mM, but fails to generate any hydrogels. 115 Nilsson et al synthesized a series of capped octapeptides (Ac-XKXKXKXK-NH 2 ; X = Val ( 270a ), Ile ( 270b ), Phe ( 270c ), F5 Phe ( 270d ), and cyclohexylalanine (Cha) ( 270e )) that are composed of alternating hydrophobic residues (Val) and positively charged residues (Lys). At 8 mM, 270a is too hydrophilic to form a hydrogel, but 270b , 270c , 270d , or 270e self-assembles in water to form a hydrogel.…”
Section: Molecular Designmentioning
confidence: 99%
“…Replacing the Cys by a Met residue allows the formation of nanofibers at 1.7 mM, but fails to generate any hydrogels. 115 Nilsson et al synthesized a series of capped octapeptides (Ac-XKXKXKXK-NH 2 ; X = Val ( 270a ), Ile ( 270b ), Phe ( 270c ), F5 Phe ( 270d ), and cyclohexylalanine (Cha) ( 270e )) that are composed of alternating hydrophobic residues (Val) and positively charged residues (Lys). At 8 mM, 270a is too hydrophilic to form a hydrogel, but 270b , 270c , 270d , or 270e self-assembles in water to form a hydrogel.…”
Section: Molecular Designmentioning
confidence: 99%
“…A self‐assembling peptide sequence, Ac‐C(FKFE) 2 CG‐NH 2 , cyclized via disulfide bonding of the flanking cysteine residues has been shown to self‐assemble into fibrillar structures upon reduction of the disulphide bond . In another report, Ac‐I 3 CGK‐NH 2 , a cysteine‐containing small peptide, formed hydrogels at low concentrations under an oxidative environment, where their mechanical properties have been tuned via degree of oxidation . Of these chemical stimuli‐responsive supramolecular hydrogels, redox‐responsive supramolecular hydrogels have been extensively studied, especially for their self‐healing property and potential applications as actuators .…”
Section: Chemical Stimulimentioning
confidence: 99%
“…[162] In another report, Ac-I 3 CGK-NH 2 , a cysteine-containing small peptide, formed hydrogels at low concentrations under an oxidative environment, where their mechanical properties have been tuned via degree of oxidation. [167] Of these chemical stimuli-responsive supramolecular hydrogels, redox-responsive supramolecular hydrogels have been extensively studied, especially for their self-healing property and potential applications as actuators. [168,169] Using redox stimuli-triggered gel–sol transition of olsalazine-containing supramolecular hydrogel, a site-specific delivery of anti-inflammatory drug was shown by Li et al [170] In another study, Wojciechowski et al have shown temporal control over transient gelation of redox-triggered supramolecular hydrogelators by tuning the competing kinetics of dissolution and gelation, thus expanding the scope of chemical stimuli-responsive supramolecular hydrogels.…”
Section: Chemical Stimulimentioning
confidence: 99%
“…Increased ionic strength in some cases also triggers self-assembly, as reported by Goldberger et al (2011[ 29 ]) that 5 mM Ca 2+ renders morphological transition to form nanofibers. In addition, introducing functional groups into precursors allow certain chemical reactions, such as hydrolysis (Zhao et al, 2011[ 114 ]), redox reactions (Chen et al, 2012[ 8 ]; Cao et al, 2012[ 7 ]), and photochemical reactions (Yamamoto et al,1999[ 99 ]), to take place, which are useful types of triggering mechanisms for controlling intermolecular interactions and initiating self-assembly.…”
Section: Triggers For Making Non-covalent Supramolecular Biomaterialsmentioning
confidence: 99%